(untitled)
During the last decades, the western center of the province of Buenos Aires registered a significant increase of the grain cultivation area due to the increase of the demand of cereals and oil crops and to the technological innovations. There are indications which show that that process was favored by the increase in the precipitations which started in the beginings of the 60. From this, a study of the changes of the precipitations in the area was carried out, with the purpose to evaluate its influence in the process. In the evaluated period (1918/2000), it could be verified that, according to the indicated works oi investigation made previously, the region presented a cycle of long duration with damp and dry phases, separated by phases of transition, that extended approximately during the following periods: 1